Desenvolvimento e validação de método multirresidual para determinação de agrotóxicos em mel por cromatografia líquida de ultra eficiência acoplada a espectrometria de massas em série - Silva, Renata Aparecida Gonçalves (2020)
Pesticides are widely used in crops to optimize the production but are considered responsible for the decline in the pollinator population, such as bees. Therefore, bee products are likely to be contaminated with pesticide residues. Honey, one of the main bee products, was studied in this work. Thus, we sought to develop and validate a multiresidue method for the determination of the acephate, acetamiprid, carbendazim, diflubenzuron, imidacloprid, metomil and thiamethoxam in honey samples. The pesticide residues were extracted using the LLE-LTP and QuEChERS methods, followed by the dispersive cleaning step, in which magnesium sulfate and C18 were used. After extraction, the honey extracts were analyzed by UHPLC-ESI-MS/MS. The QuEChERS method consisted of weighing 5.0 g of honey sample in a polypropylene tube, adding 5 mL of Type I water and 4 mL of acetonitrile, followed by stirring. The pesticide residues from the aqueous phase of the sample were partitioned into an organic solvent by adding 6.0 g of magnesium sulfate and 1.5 g of sodium acetate under stirring. The extract was isolated by centrifugation. The extracts were purified through the dispersive cleaning step, where 1 mL of the extract was transferred to another tube containing 150 mg of anhydrous magnesium sulfate and 50 mg of C18, followed by vortex and filtration. The conditions of the LLE-LTP method were optimized using a central composite design. The optimal conditions for maximum pesticide recoveries were: 3,000 g of honey sample, 4 mL of acetonitrile solvent and 180 minutes of freezing. Then, extracts from the QuEChERS and LLE-LTP methods were filtered and analyzed by UHPLC-MS/MS. The methodology was validated according to the SANTE/11813/2017 document, evaluating the linearity, limits of detection and quantification, matrix effect, selectivity, uncertainty, accuracy, and precision. The recoveries were in the range of 70 to 120 % for the studied pesticides, except for the acephate by the LLE-LTP method, while the RSD was less than 20 % for all pesticides. The limit of quantification for pesticides was between 2.0 and 6.7 μg kg-1, indicating the high detectability of the developed methodologies. Honey samples from the Triângulo Mineiro region were evaluated by methodologies, detecting pesticide residues in all samples, always at levels below the permitted maximum residual limits, highlighting the high detectability of the proposed methodologies.